A First-Principles Study of the Structural, Elastic, and Mechanical Characteristics of Mg2Ni Subjected to Pressure Conditions - Chuncai Xiao; Lei Liu; Shihuan Liu; Zhangli Lai; Yuxin Liu; Xianshi Zeng; Luliang Liao (Metals, 2024)
This study employs first-principles calculations to examine structural, elastic, and mechanistic relationships of Mg2Ni alloys under varying conditions of pressure. The investigation encompasses Young’s modulus, bulk modulus, shear modulus, Poisson’s ratio, and anisotropy index, as well as sound velocity, Debye temperature, and related properties. Our findings indicate that the lattice parameters of Mg2Ni in its ground state are in agreement with values obtained experimentally and from the literature, confirming the reliability of the calculated results. Furthermore, a gradual decrease in the values of the lattice parameters <semantics>a/a0</semantics> and <semantics>c/c0</semantics> is observed with increasing pressure. Specifically, the values for <semantics>C13</semantics> and <semantics>C33</semantics> decrease at a hydrostatic pressure of 5 GPa, while <semantics>C11</semantics> and <semantics>C13</semantics> increase when the external hydrostatic pressure exceeds 5 GPa. All other elastic constants exhibit a consistent increasing trend with increasing pressure between 0 and 30 GPa, with <semantics>C11</semantics> and <semantics>C12</semantics> increasing at a faster rate than <semantics>C44</semantics> and <semantics>C66</semantics>. In the 0–30 GPa pressure range, Mg2Ni satisfies the mechanical stability criterion, indicating its stable existence under these conditions. Additionally, the Poisson’s ratio of Mg2Ni consistently exceeds 0.26 over a range of pressures from 0 to 30 GPa, signifying ductility and demonstrating consistency with the value of <semantics>B/G</semantics>. The hardness of Mg2Ni increases within the pressure range of 0–5 GPa, but decreases above 5 GPa. Notably, the shear anisotropy of Mg2Ni exhibits greater significance than the compressive anisotropy, with its anisotropy intensifying under higher pressures. Both the sound anisotropy and the Debye temperature of Mg2Ni demonstrate an increasing trend with rising pressure.